Advanced Digital Organic Vehicle Security System - Rathod, Arun Pratap Singh; Mittal, Poornima; Kumar, Brijesh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*293.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913618);" role="presentation">This paper is about presenting an economical and simple vehicle security system by which a vehicle can identify <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*306.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908482);" role="presentation">its user and provide security against any unauthorized access to the vehicle. In this paper we have designed and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*319.85px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92709);" role="presentation">implemented a simple digital interface (DI) at the front end which when placed between car battery and ignition <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*333.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952196);" role="presentation">system it makes the vehicle smart enough to identify its user with help of a security PIN. Further this vehicle <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.880458);" role="presentation">system <span dir="ltr" style="left: calc(var(--scale-factor)*105.97px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94692);" role="presentation">utilizes <span dir="ltr" style="left: calc(var(--scale-factor)*140.87px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917039);" role="presentation">organic <span dir="ltr" style="left: calc(var(--scale-factor)*177.05px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89304);" role="presentation">transistors <span dir="ltr" style="left: calc(var(--scale-factor)*224.41px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95375);" role="presentation">which <span dir="ltr" style="left: calc(var(--scale-factor)*254.86px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976547);" role="presentation">itself <span dir="ltr" style="left: calc(var(--scale-factor)*280.98px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.847983);" role="presentation">are <span dir="ltr" style="left: calc(var(--scale-factor)*299.32px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930983);" role="presentation">quite <span dir="ltr" style="left: calc(var(--scale-factor)*325.56px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938039);" role="presentation">innovative <span dir="ltr" style="left: calc(var(--scale-factor)*373.86px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*394.61px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981602);" role="presentation">widely <span dir="ltr" style="left: calc(var(--scale-factor)*427.82px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.851211);" role="presentation">used <span dir="ltr" style="left: calc(var(--scale-factor)*452.38px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.788658);" role="presentation">as <span dir="ltr" style="left: calc(var(--scale-factor)*466.77px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918201);" role="presentation">alternative <span dir="ltr" style="left: calc(var(--scale-factor)*515.09px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*359.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943716);" role="presentation">conventional MOSFETs for cost efficient applications. Here too we have utilized them to make DI economical <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*372.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942274);" role="presentation">in cost and robust in nature to overcome much troubled issue of modern times i.e. stealing of vehicles with or <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*385.99px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93189);" role="presentation">without vehicle keys.